Corrosion-resistant marine photovoltaic support composite coating and preparation method thereof
By using a composite coating system with hot-dip galvanized layer or zinc-aluminum-magnesium plating combined with polyester powder coating on offshore photovoltaic brackets, the corrosion problem of offshore photovoltaic brackets in the marine environment is solved, and the corrosion resistance and use are significantly improved. Lifespan and provides electrochemical protection at scratches.
Patent Information
- Application Number
- CN202411243152.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-13
AI Technical Summary
Offshore photovoltaic brackets face problems such as corrosion, physical damage, electromagnetic interference, temperature fluctuations and electrolytic corrosion in the marine environment, and the existing technology is difficult to significantly improve its corrosion resistance.
A composite coating system adopts hot-dip galvanized layer or zinc-aluminum-magnesium plating layer combined with polyester powder coating. The thickness of the hot-dip plating layer is 40-100μm, and the thickness of the polyester powder coating is 100-150μm. The coating contains hyperbranched poly Ester resin, curing agent, leveling agent, benzoin, brightener, titanium dioxide, flake-like filler, zinc phosphate hydrate and organic corrosion inhibitor, improve the heat resistance and chemical resistance of the coating through esterification and polycondensation reactions Corrosive.
It significantly improves the corrosion resistance and service life of offshore photovoltaic stents. The composite coating system can provide long-term protection in CX environment, extends the service life of the coating, and provides good electrochemical protection at scratches.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of offshore photovoltaic surface anticorrosion, and in particular to a corrosion-resistant offshore photovoltaic bracket composite coating and a preparation method thereof. Background Art
[0002] The total length of my country's coastline exceeds 18,000 kilometers. Theoretically, the ocean area that can be developed for photovoltaic projects can reach 710,000 square kilometers, and more than 100 GW of offshore photovoltaics can be installed.
[0003] Difficulties of offshore photovoltaic power generation: Salt spray, humidity, and wave scouring in the marine environment can cause corrosion to equipment and brackets, affecting the service life of the equipment. The specific analysis is as follows:
[0004] 1) Corrosion: Seawater contains salt, which can corrode materials and components of photovoltaic systems. For example, components exposed to seawater for a long time may cause material performance degradation or even damage.
[0005] 2) Physical damage: The wind, waves and currents at sea exert forces on the housing and support structure of the photovoltaic system, and additional design may be required to ensure the stability and durability of the system. The fixed support and tracking system need to be able to withstand harsh sea conditions.
[0006] 3) Electromagnetic interference: There are a large number of electromagnetic interference sources in the marine environment, such as marine aircraft, navigation equipment, etc., which may affect the electromagnetic compatibility (EMC) of the photovoltaic system. Shielding and filtering measures need to be considered during design to reduce the adverse effects of external interference on system performance.
[0007] 4) Temperature fluctuation: The ocean environment temperature varies greatly, and the temperature difference between day and night may cause fluctuations in the performance of photovoltaic modules. This temperature spectrum change needs to be considered in the performance calculation and optimization of the system.
[0008] 5) Anti-corrosion and moisturizing: In order to prevent photovoltaic modules and related equipment from being corroded by the marine environment, appropriate anti-corrosion treatment must be taken, and the equipment needs to maintain an appropriate humidity to prevent material damage and performance degradation.
[0009] 6) Electrolytic corrosion: Electrolytic corrosion is another challenge facing offshore PV modules. To reduce the risk of electrolytic corrosion, measures can be taken, such as using connectors made of different materials and isolating metal parts to reduce the potential difference between different metals, thereby reducing the possibility of corrosion.
[0010] In order to improve the corrosion resistance of offshore photovoltaic brackets, the commonly used methods are:
[0011] 1) Hot-dip galvanized coating, but according to ISO1461 and ISO9224 standards, 500-600g / m2 Hot-dip galvanized coatings can only survive less than 5 years in CX environments.
[0012] 2) Zinc-aluminum-magnesium coating: There is no recognized corrosion calculation standard. Usually, the corrosion resistance of a plate of the same thickness is 2-3 times that of a galvanized layer. It can only be calculated according to the corrosion rate of hot-dip galvanizing in the ISO9224 standard, 450g / m 2 The anti-corrosion life of zinc-aluminum-magnesium coating is no more than 15 years. At the same time, the self-repair function of zinc-aluminum-magnesium coating cutting edge needs more time and application to verify.
[0013] Therefore, there is an urgent need for a method that can significantly improve the corrosion resistance of offshore photovoltaic brackets. Summary of the invention
[0014] The purpose of the present invention is to provide a corrosion-resistant offshore photovoltaic support composite coating and a preparation method thereof, so as to solve at least one of the above-mentioned technical problems.
[0015] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0016] A corrosion-resistant composite coating for an offshore photovoltaic support, the composite coating comprising a hot-dip coating disposed on a surface of the photovoltaic support and a polyester powder coating disposed on a surface of the hot-dip coating;
[0017] The hot-dip coating is selected from a hot-dip galvanizing layer and a zinc-aluminum-magnesium coating;
[0018] The thickness of the hot-dip galvanized layer is 40-100 μm, and the coating mass of the hot-dip galvanized aluminum-magnesium layer is 250-300 g / m 2 ,
[0019] The polyester powder coating has a thickness of 100-150 μm.
[0020] Furthermore, the polyester powder coating has the following composition by weight:
[0021] Hyperbranched polyester resin 60%, curing agent 15%, leveling agent 1%, benzoin 0.5%, brightener 1%, titanium dioxide 20%, flaky pigment 6.5%, zinc phosphate hydrate 3.5%, organic corrosion inhibitor 0.5%, curing agent 21%, silane coupling agent 1%.
[0022] Specifically, the curing agent 1 is selected from one of tri-β-methyl glycidyl isocyanurate and hydroxyalkylamide curing agent;
[0023] The leveling agent is selected from one of acrylate homopolymer and silicone modified acrylate polymer;
[0024] The brightener is selected from one of polyethylene wax, polypropylene wax and silicone brightener;
[0025] The flake pigment filler is used to delay the time for ions to penetrate into the substrate, and one of aluminum powder or mica titanium pearlescent pigment is selected;
[0026] The organic corrosion inhibitor is used to improve the salt spray performance, and one of polyethylene diamine and polypropylene diamine is selected;
[0027] Curing agent 2 is used to cure the hyperbranched hydroxyl groups and increase the crosslinking density, and toluene diisocyanate is selected;
[0028] The silane coupling agent is used to improve adhesion, and one of vinyl trimethoxy silane and γ-glycidyloxypropyl trimethoxy silane is selected.
[0029] Furthermore, the preparation method of the hyperbranched polyester resin comprises the following steps:
[0030] S1 esterification reaction: add terephthalic acid, neopentyl glycol, organotin catalyst and polymerization inhibitor into a reaction vessel, raise the temperature to 180-220°C for esterification reaction, and the esterification reaction time is 8-10 hours;
[0031] S2 polycondensation reaction: After the esterification reaction is completed, the temperature is lowered to 200-220°C, and isophthalic acid, polydimethylsilane and a catalyst are added to carry out a polycondensation reaction. The reaction time is 6-8 hours. By introducing silicone functional groups, the heat resistance, chemical corrosion resistance and mechanical strength of the polyester resin can be significantly improved.
[0032] Furthermore, the organic tin catalyst is a sulfur-containing catalyst, and one of dibutyltin isooctyl dithioacetate, dimethyltin isooctyl dithioacetate, and dioctyltin isooctyl dithioacetate is selected;
[0033] The polymerization inhibitor is selected from one of p-hydroxyanisole and 2-tert-butylhydroquinone.
[0034] Furthermore, in step S1, the amount of the organic tin catalyst added is 0.01-0.05% of the total mass of terephthalic acid and neopentyl glycol, the amount of the polymerization inhibitor added is 0.001%-0.1% of the total mass of terephthalic acid and neopentyl glycol, and the molar ratio of terephthalic acid to neopentyl glycol is 1:2.
[0035] Further, the molar ratio of the amount of isophthalic acid added in step S2 to the amount of terephthalic acid added in step S1 is 1:1;
[0036] The amount of polydimethylsilane added in step S2 is 1-5% of the product in step S1.
[0037] The catalyst in step S2 is a mixture of titanium alkoxide, tin oxide, antimony trioxide and cadmium acetate, with a molar ratio of 1:0.5:0.3:0.6.
[0038] Furthermore, the preparation method of the polyester powder comprises the following steps:
[0039] 1) Prepare the above raw materials in proportion, add them in layers, and premix them at high speed;
[0040] 2) Melt mixing extrusion: The extrusion temperature of the twin screw zone 1 is 100-120°C, the extrusion temperature of the second zone is 120-130°C, the extrusion temperature of the third zone is 110-120°C, the main screw frequency is 40-50HZ, and the feeding speed is 25-40hz;
[0041] 3) Cool and crush the tablets into pieces with a thickness of 1 to 2 mm and an average area of 1 ± 0.2 cm 2 The flakes are ground into polyester powder, which is ground by a cyclone separation mill with a main mill frequency of 45-50 Hz, a classifier frequency of 20-35 Hz, and a feed frequency of 20-40 Hz.
[0042] A method for preparing a corrosion-resistant offshore photovoltaic support composite coating, the preparation method comprising the following steps:
[0043] S1 performs hot-dip galvanizing on the solar photovoltaic bracket and then performs surface treatment before spraying, which specifically includes the following steps:
[0044] 1) Hot-dip galvanizing process: The workpiece is placed in hydrochloric acid with corrosion inhibitor and degreasing agent added to remove oil and rust on the surface of the workpiece, then rinsed with clean water, and then immersed in a mixed plating solution of ammonium chloride (mass percentage of 20%) and zinc chloride (mass percentage of 30%). After being taken out and dried, it is placed in a molten zinc solution at a temperature of 435-455°C for 2-10 minutes. After being taken out, it is placed in clean water at a temperature not exceeding 60°C to cool, and then taken out and drained;
[0045] 2) Surface treatment before spraying: chemical treatment is adopted, and the workpiece is driven into the channel of the spray device through the conveyor chain. After 1.5 minutes of high-pressure spraying at 0.1Mpa, the cleaning of each process is completed in sequence. First, the degreasing process is entered. The degreasing liquid is diluted with water in proportion and heated to 50°C. The main purpose is to remove oil stains and stains on the surface of the workpiece. Then, the degreasing liquid remaining on the surface is rinsed with tap water to avoid contamination of the phosphating liquid. Then, the phosphating liquid is diluted with water in proportion and heated appropriately according to the change of ambient temperature to generate a conversion film on the surface of the workpiece to enhance the adhesion with the coating. Finally, it is rinsed with tap water to avoid the residue of the phosphating liquid. After rinsing, the workpiece enters the 80°C drying channel, and after drying the residual water on the surface, it enters the next process;
[0046] S2 spraying polyester powder coating: The spraying process is carried out using an electrostatic spray gun in a spray room with a recovery system. The thickness of the polyester powder spray coating is 100-150μm.
[0047] S3 baking: baking is carried out according to the powder solidification process, the workpiece temperature is 200°C, and the baking time is 10 to 15 minutes.
[0048] Beneficial effects:
[0049] In the present invention, a composite coating of a hot-dip coating and a polyester coating is provided on the offshore photovoltaic bracket. The two coatings have a synergistic effect, and the service life is longer than the sum of the service lives of the individual coatings. The service life relationship satisfies the following formula:
[0050] Coating Synergy:Life total =K·(Life Zn +Life coating )
[0051] The synergy factor K in the formula is related to the weather to which it is exposed - corrosive atmosphere: K = 1.8–2.0; general atmosphere: K = 2.0–2.7.
[0052] After 4200 hours of cyclic aging test, the super weather-resistant polyester hot-dip galvanized composite coating system of the present invention has a rust grade of Ri0 and a peeling grade of S0. This indicates that the composite coating system can provide long-term protection for steel in a CX environment, and the hot-dip galvanized layer in the coating system can provide good electrochemical protection for the exposed substrate at the scratches, that is, when the steel substrate is exposed due to slight scratches and bumps during installation and transportation, the coating system can still provide good protection for it. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is a picture of the 5-cycle aging test of the composite coating in Example 1 of the present invention.
[0054] Figure 2 This is a picture of the 10-cycle aging test of the composite coating in Example 1 of the present invention.
[0055] Figure 3 This is a picture of the 15-cycle aging test of the composite coating in Example 1 of the present invention.
[0056] Figure 4 This is a picture of the 20-cycle aging test of the composite coating in Example 1 of the present invention.
[0057] Figure 5 This is a picture of the 25-cycle aging test of the composite coating in Example 1 of the present invention.
[0058] Figure 6This is a picture of the composite coating in Example 1 of the present invention being stripped of the coating and slightly polished off the corrosion products.
[0059] Figure 7 This is a picture of the cyclic aging scratch test of the composite coating in Example 1 of the present invention. DETAILED DESCRIPTION
[0060] The present invention will now be described in further detail in conjunction with specific embodiments. The following embodiments may enable those skilled in the art to more fully understand the present invention, but these embodiments are not intended to limit the scope of protection of the present invention. "One embodiment" or "embodiment" referred to herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. "In one embodiment" appearing in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0061] Example 1
[0062] A corrosion-resistant offshore photovoltaic support composite coating comprises a hot-dip galvanizing layer arranged on the surface of the photovoltaic support and a polyester powder coating arranged on the surface of the hot-dip galvanizing layer; the thickness of the hot-dip galvanizing layer is 40 μm, and the thickness of the polyester powder coating is 100 μm.
[0063] The polyester powder coating has the following composition by weight:
[0064] Hyperbranched polyester resin 60%, curing agent 15%, leveling agent 1%, benzoin 0.5%, brightener 1%, titanium dioxide 20%, flaky pigment 6.5%, zinc phosphate hydrate 3.5%, organic corrosion inhibitor 0.5%, curing agent 21%, silane coupling agent 1%.
[0065] Specifically, the curing agent 1 is tri-β-methyl glycidyl isocyanurate;
[0066] The leveling agent is acrylate homopolymer;
[0067] The brightener is polyethylene wax;
[0068] Flaky pigments and fillers are used to delay the time for ions to penetrate into the base material, and aluminum powder is used;
[0069] Organic corrosion inhibitor is used to improve salt spray performance, and polyethylene diamine is selected;
[0070] Curing agent 2 is used to cure the hyperbranched hydroxyl groups and increase the crosslinking density, and toluene diisocyanate is selected;
[0071] Silane coupling agents are used to improve adhesion, and vinyltrimethoxysilane is selected.
[0072] Wherein, the preparation method of hyperbranched polyester resin comprises the following steps:
[0073] S1 esterification reaction: terephthalic acid, neopentyl glycol, organotin catalyst and polymerization inhibitor were added into the reaction vessel, and the temperature was raised to 180°C for esterification reaction. The esterification reaction time was 10 hours;
[0074] The organic tin catalyst is a sulfur-containing catalyst, and dibutyltin isooctyl dithioacetate is selected;
[0075] The inhibitor is p-hydroxyanisole.
[0076] In step S1, the amount of the organic tin catalyst added is 0.01% of the total mass of terephthalic acid and neopentyl glycol, the amount of the polymerization inhibitor added is 0.001% of the total mass of terephthalic acid and neopentyl glycol, and the molar ratio of terephthalic acid to neopentyl glycol is 1:2.
[0077] S2 polycondensation reaction: After the esterification reaction is completed, the temperature is lowered to 200°C, and isophthalic acid, polydimethylsilane and a catalyst are added for a polycondensation reaction. The reaction time is 8 hours. By introducing silicone functional groups, the heat resistance, chemical corrosion resistance and mechanical strength of the polyester resin can be significantly improved.
[0078] The amount of isophthalic acid added in step S2 is 1:1 in the molar ratio of terephthalic acid in step S1;
[0079] The amount of polydimethylsilane added in step S2 is 1% of the product in step S1.
[0080] The catalyst in step S2 is a mixture of titanium alkoxide, tin oxide, antimony trioxide and cadmium acetate in a molar ratio of 1:0.5:0.3:0.6.
[0081] Specifically, the preparation method of polyester powder comprises the following steps:
[0082] 1) Prepare the above raw materials in proportion, add them in layers, and premix them at high speed;
[0083] 2) Melt mixing extrusion: the extrusion temperature of the twin screw zone 1 is 100°C, the extrusion temperature of the second zone is 120°C, the extrusion temperature of the third zone is 120°C, the main screw frequency is 40HZ, and the feeding speed is 25hz;
[0084] 3) Cool and crush the tablets into pieces with a thickness of 1 mm and an average area of 1.2 cm 2 The flakes are ground into polyester powder, which is ground using a cyclone separation mill with a main mill frequency of 45 Hz, a classifier frequency of 20 Hz, and a feed frequency of 20 Hz.
[0085] The method for preparing the corrosion-resistant offshore photovoltaic bracket composite coating in this embodiment comprises the following steps:
[0086] S1 performs hot-dip galvanizing on the solar photovoltaic bracket and then performs surface treatment before spraying, which specifically includes the following steps:
[0087] 1) Hot-dip galvanizing process: The workpiece is placed in hydrochloric acid to which a corrosion inhibitor and a degreasing agent are added to remove oil and rust on the surface of the workpiece, and then rinsed with clean water, and then immersed in a mixed plating solution of ammonium chloride (20% by mass) and zinc chloride (30% by mass), taken out and dried, and then placed in a molten zinc solution at a temperature of 435° C. for 10 minutes. After being taken out, it is placed in clean water at a temperature not exceeding 60° C. (55° C. in this embodiment) to cool, and then taken out and drained;
[0088] 2) Surface treatment before spraying: chemical treatment is adopted, and the workpiece is driven into the channel of the spray device through the conveyor chain. After 1.5 minutes of high-pressure spraying at 0.1Mpa, the cleaning of each process is completed in sequence. First, the degreasing process is entered. The degreasing liquid is diluted with water in proportion and heated to 50°C. The main purpose is to remove oil stains and stains on the surface of the workpiece. Then, the degreasing liquid remaining on the surface is rinsed with tap water to avoid contamination of the phosphating liquid. Then, the phosphating liquid is diluted with water in proportion and heated appropriately according to the change of ambient temperature to generate a conversion film on the surface of the workpiece to enhance the adhesion with the coating. Finally, it is rinsed with tap water to avoid the residue of the phosphating liquid. After rinsing, the workpiece enters the 80°C drying channel, and after drying the residual water on the surface, it enters the next process;
[0089] S2 spraying polyester powder coating: The spraying process is carried out using an electrostatic spray gun in a spray room with a recovery system.
[0090] S3 baking: baking is carried out according to the powder solidification process, the workpiece temperature is 200°C, and the baking time is 10 minutes.
[0091] The pictures of the 5-cycle aging test of the composite coating in this embodiment are shown in Figure 1 .
[0092] The pictures of the 10-cycle aging test of the composite coating in this embodiment are shown in Figure 2 .
[0093] The pictures of the 15-cycle aging test of the composite coating in this embodiment are shown in Figure 3 .
[0094] The pictures of the 20-cycle aging test of the composite coating in this embodiment are shown in Figure 4 .
[0095] The pictures of the 25-cycle aging test of the composite coating in this embodiment are shown in Figure 5 .
[0096] In this embodiment, the composite coating is stripped and the corrosion products are slightly polished off. Figure 6.
[0097] The pictures of the composite coating cyclic aging scratch test in this embodiment are shown in Figure 7 .
[0098] Example 2
[0099] A corrosion-resistant composite coating for an offshore photovoltaic support comprises a hot-dip coating arranged on the surface of the photovoltaic support and a polyester powder coating arranged on the surface of the hot-dip coating; the thickness of the hot-dip coating is 70 μm, and the thickness of the polyester powder coating is 120 μm.
[0100] The polyester powder coating has the following composition by weight:
[0101] Hyperbranched polyester resin 60%, curing agent 15%, leveling agent 1%, benzoin 0.5%, brightener 1%, titanium dioxide 20%, flaky pigment 6.5%, zinc phosphate hydrate 3.5%, organic corrosion inhibitor 0.5%, curing agent 21%, silane coupling agent 1%.
[0102] Specifically, the curing agent 1 is tri-β-methyl glycidyl isocyanurate;
[0103] The leveling agent is silicone-modified acrylate polymer;
[0104] The brightener is polypropylene wax;
[0105] Flaky pigments and fillers are used to delay the time for ions to penetrate into the substrate, and mica titanium pearlescent pigments are used;
[0106] Organic corrosion inhibitor is used to improve salt spray performance, and polyethylene diamine is selected;
[0107] Curing agent 2 is used to cure the hyperbranched hydroxyl groups and increase the crosslinking density, and toluene diisocyanate is selected;
[0108] Silane coupling agents are used to improve adhesion, and vinyltrimethoxysilane is selected.
[0109] Specifically, the preparation method of the hyperbranched polyester resin comprises the following steps:
[0110] S1 esterification reaction: terephthalic acid, neopentyl glycol, organotin catalyst and polymerization inhibitor were added into the reaction vessel, and the temperature was raised to 200°C for esterification reaction. The esterification reaction time was 90 hours;
[0111] The organic tin catalyst is a sulfur-containing catalyst, and dimethyltin dithioacetate isooctyl ester is selected;
[0112] The inhibitor is p-hydroxyanisole;
[0113] The amount of the organic tin catalyst added is 0.03% of the total mass of terephthalic acid and neopentyl glycol, the amount of the polymerization inhibitor added is 0.05% of the total mass of terephthalic acid and neopentyl glycol, and the molar ratio of terephthalic acid to neopentyl glycol is 1:2.
[0114] S2 polycondensation reaction: After the esterification reaction is completed, the temperature is lowered to 220°C, and isophthalic acid, polydimethylsilane and a catalyst are added to carry out a polycondensation reaction. The reaction time is 7 hours. By introducing silicone functional groups, the heat resistance, chemical corrosion resistance and mechanical strength of the polyester resin can be significantly improved.
[0115] The amount of isophthalic acid added in step S2 is 1:1 in the molar ratio of terephthalic acid in step S1;
[0116] The amount of polydimethylsilane added in step S2 is 3% of the product in step S1.
[0117] The catalyst in step S2 is a mixture of titanium alkoxide, tin oxide, antimony trioxide and cadmium acetate in a molar ratio of 1:0.5:0.3:0.6.
[0118] Furthermore, the preparation method of the polyester powder comprises the following steps:
[0119] 1) Prepare the above raw materials in proportion, add them in layers, and premix them at high speed;
[0120] 2) Melt mixing extrusion: the extrusion temperature of the twin screw zone 1 is 110°C, the extrusion temperature of the second zone is 125°C, the extrusion temperature of the third zone is 115°C, the main screw frequency is 45HZ, and the feeding speed is 30hz;
[0121] 3) Cool and crush the tablets into pieces with a thickness of 1.5 mm and an average area of 1 cm 2 The flakes are ground into polyester powder, which is ground using a cyclone separation mill with a main mill frequency of 48 Hz, a classifier of 30 Hz, and a feeder of 30 Hz.
[0122] The method for preparing the corrosion-resistant offshore photovoltaic bracket composite coating in this embodiment comprises the following steps:
[0123] S1 performs hot-dip galvanizing on the solar photovoltaic bracket and then performs surface treatment before spraying, which specifically includes the following steps:
[0124] 1) Hot-dip galvanizing process: the workpiece is placed in hydrochloric acid added with a corrosion inhibitor and a degreasing agent to remove oil and rust on the surface of the workpiece, then rinsed with clean water, and then immersed in a mixed plating solution of ammonium chloride (mass percentage of 25%) and zinc chloride (mass percentage of 25%), taken out and dried, and then placed in a molten zinc solution at a temperature of 445° C. for 8 minutes. After being taken out, it is placed in clean water at a temperature not exceeding 60° C. (50° C. in this embodiment) to cool, and then taken out and drained;
[0125] 2) Surface treatment before spraying: chemical treatment is adopted, and the workpiece is driven into the channel of the spray device through the conveyor chain. After 1.5 minutes of high-pressure spraying at 0.1Mpa, the cleaning of each process is completed in sequence. First, the degreasing process is entered. The degreasing liquid is diluted with water in proportion and heated to 50°C. The main purpose is to remove oil stains and stains on the surface of the workpiece. Then, the degreasing liquid remaining on the surface is rinsed with tap water to avoid contamination of the phosphating liquid. Then, the phosphating liquid is diluted with water in proportion and heated appropriately according to the change of ambient temperature to generate a conversion film on the surface of the workpiece to enhance the adhesion with the coating. Finally, it is rinsed with tap water to avoid the residue of the phosphating liquid. After rinsing, the workpiece enters the 80°C drying channel, and after drying the residual water on the surface, it enters the next process;
[0126] S2 spraying polyester powder coating: The spraying process is carried out using an electrostatic spray gun in a spray room with a recovery system.
[0127] S3 baking: baking is carried out according to the powder solidification process, the workpiece temperature is 200°C, and the baking time is 12 minutes.
[0128] Example 3
[0129] A corrosion-resistant composite coating for an offshore photovoltaic support comprises a hot-dip coating arranged on the surface of the photovoltaic support and a polyester powder coating arranged on the surface of the hot-dip coating; the thickness of the hot-dip coating is 100 μm, and the thickness of the polyester powder coating is 120 μm.
[0130] The polyester powder coating has the following composition by weight:
[0131] Hyperbranched polyester resin 60%, curing agent 15%, leveling agent 1%, benzoin 0.5%, brightener 1%, titanium dioxide 20%, flaky pigment 6.5%, zinc phosphate hydrate 3.5%, organic corrosion inhibitor 0.5%, curing agent 21%, silane coupling agent 1%.
[0132] Specifically, the curing agent 1 is a hydroxyalkylamide curing agent;
[0133] The leveling agent is silicone-modified acrylate polymer;
[0134] The brightener is silicone brightener;
[0135] Flaky pigments and fillers are used to delay the time for ions to penetrate into the substrate, and mica titanium pearlescent pigments are used;
[0136] Organic corrosion inhibitor is used to improve salt spray performance, and polypropylene diamine is selected;
[0137] Curing agent 2 is used to cure the hyperbranched hydroxyl groups and increase the crosslinking density, and toluene diisocyanate is selected;
[0138] Silane coupling agents are used to improve adhesion, and γ-glycidyloxypropyltrimethoxysilane is selected.
[0139] Wherein, the preparation method of hyperbranched polyester resin comprises the following steps:
[0140] S1 esterification reaction: terephthalic acid, neopentyl glycol, organotin catalyst and polymerization inhibitor were added into the reaction vessel, and the temperature was raised to 210°C for esterification reaction. The esterification reaction time was 8 hours;
[0141] The polymerization inhibitors are p-hydroxyanisole and 2-tert-butylhydroquinone.
[0142] In step S1, the amount of the organic tin catalyst added is 0.05% of the total mass of terephthalic acid and neopentyl glycol, the amount of the polymerization inhibitor added is 0.1% of the total mass of terephthalic acid and neopentyl glycol, and the molar ratio of terephthalic acid to neopentyl glycol is 1:2.
[0143] S2 polycondensation reaction: After the esterification reaction is completed, the temperature is lowered to 220°C, and isophthalic acid, polydimethylsilane and a catalyst are added to carry out a polycondensation reaction. The reaction time is 6 hours. By introducing silicone functional groups, the heat resistance, chemical corrosion resistance and mechanical strength of the polyester resin can be significantly improved.
[0144] The organic tin catalyst is a sulfur-containing catalyst, and dioctyltin dithioacetate is selected;
[0145] The amount of isophthalic acid added in step S2 is 1:1 in the molar ratio of terephthalic acid in step S1;
[0146] The amount of polydimethylsilane added in step S2 is 5% of the product in step S1.
[0147] The catalyst in step S2 is a mixture of titanium alkoxide, tin oxide, antimony trioxide and cadmium acetate in a molar ratio of 1:0.5:0.3:0.6.
[0148] Wherein, the preparation method of polyester powder comprises the following steps:
[0149] 1) Prepare the above raw materials in proportion, add them in layers, and premix them at high speed;
[0150] 2) Melt mixing extrusion: the extrusion temperature of the twin screw zone 1 is 120°C, the extrusion temperature of the second zone is 130°C, the extrusion temperature of the third zone is 110°C, the main screw frequency is 50HZ, and the feeding speed is 40hz;
[0151] 3) Cool the pressed tablets and break them into pieces with a thickness of 2 mm and an average area of 0.8 cm 2 The flakes are ground into polyester powder, which is ground using a cyclone separation mill with a main mill frequency of 50 Hz, a classifier of 35 Hz, and a feeder of 40 Hz.
[0152] The method for preparing the corrosion-resistant offshore photovoltaic bracket composite coating in this embodiment comprises the following steps:
[0153] S1 performs hot-dip galvanizing on the solar photovoltaic bracket and then performs surface treatment before spraying, which specifically includes the following steps:
[0154] 1) Hot-dip galvanizing process: the workpiece is placed in hydrochloric acid added with corrosion inhibitor and degreasing agent to remove oil and rust on the surface of the workpiece, then rinsed with clean water, and then immersed in a mixed plating solution of ammonium chloride (30% by mass) and zinc chloride (20% by mass), taken out and dried, and then placed in a molten zinc solution at a temperature of 455° C. for 2 minutes. After being taken out, it is placed in clean water at a temperature not exceeding 60° C. (40° C. in this embodiment) to cool, and then taken out and drained;
[0155] 2) Surface treatment before spraying: chemical treatment is adopted, and the workpiece is driven into the channel of the spray device through the conveyor chain. After 1.5 minutes of high-pressure spraying at 0.1Mpa, the cleaning of each process is completed in sequence. First, the degreasing process is entered. The degreasing liquid is diluted with water in proportion and heated to 50°C. The main purpose is to remove oil stains and stains on the surface of the workpiece. Then, the degreasing liquid remaining on the surface is rinsed with tap water to avoid contamination of the phosphating liquid. Then, the phosphating liquid is diluted with water in proportion and heated appropriately according to the change of ambient temperature to generate a conversion film on the surface of the workpiece to enhance the adhesion with the coating. Finally, it is rinsed with tap water to avoid the residue of the phosphating liquid. After rinsing, the workpiece enters the 80°C drying channel, and after drying the residual water on the surface, it enters the next process;
[0156] S2 spraying polyester powder coating: The spraying process is carried out using an electrostatic spray gun in a spray room with a recovery system.
[0157] S3 baking: baking is carried out according to the powder solidification process, the workpiece temperature is 200°C, and the baking time is 15 minutes.
[0158] 1. Test methods
[0159] The composite coatings in Examples 1 to 3 were subjected to performance tests according to ISO 12944-9 “Protective coating systems and laboratory performance test methods for offshore structures and related structures”. Artificial aging tests can be used to evaluate the durability of the coatings.
[0160] 2. Evaluation standard: Adopt a new coating anti-corrosion system, and the evaluation standard refers to ISO 12944-9 standard method
[0161]
[0162] 3. Test Results
[0163] 3.1 Adhesion test
[0164] Table 1
[0165]
[0166]
[0167] As can be seen from Table 1, the adhesion of the hot-dip galvanized layer to the carbon steel substrate is very strong due to the metallurgical bonding. The adhesion tested here is the result of the bonding between the super-weather-resistant polyester coating and the hot-dip galvanized layer. From the data in the table, it can be seen that the super-weather-resistant polyester coating has good bonding with the hot-dip galvanized layer, and its bonding can meet the standard requirements before and after the 4200-hour cycle aging test.
[0168] 3.2 Cyclic aging test
[0169] Table 2
[0170]
[0171] As can be seen from Table 2, after 4200 hours of cyclic aging test, the rust level and peeling level of the coating system are Ri0 and Ri0, respectively. However, it can also be observed from the figure that a small amount of blistering occurs in the coating, and at the same time, obvious coating warping and cracking, as well as yellow rust spots, occur near the scribed area. It should be noted that the blistering of this sample is significantly different from the coating blistering specified in ISO12944. This is because the blistering of this sample occurs between the coating and the galvanized layer, not between the coating and the steel substrate. The blistering of the coating does not mean that the steel substrate is corroded.
[0172] Table 3 Test results of the galvanized layer thickness near the coating blistering and cracking parts and the scribed parts
[0173]
[0174]
[0175] In order to verify whether the steel substrate is corroded at the blistering, cracking and yellow spots of the coating, the coating at these locations is removed and the corrosion products are lightly polished to remove them, and the thickness of the galvanized layer is measured as shown in the table above. From the results in Table 3, it can be seen that these locations still have a thickness of more than 70 microns. The yellow rust spots are yellow corrosion products formed after the iron-zinc alloy layer in the hot-dip galvanized layer is corroded due to the high content of iron in it. The results show that after 4200 hours of cyclic aging test, the anti-corrosion coating system in this test can completely protect the steel substrate from corrosion; and the hot-dip galvanized layer under the coating still has a high thickness, which can continue to provide protection for the carbon steel substrate.
[0176] 3.3 Cyclic aging scratch test
[0177] Depend on Figure 7 It can be seen that the scratched part has been damaged to the substrate (carbon steel) during the scratching process. Since this sample has a hot-dip galvanized layer, the scratched and damaged carbon steel substrate did not rust after 4200 hours of cyclic aging test, indicating that the hot-dip galvanized layer provides good electrochemical protection for the exposed substrate at the scratch.
[0178] In summary, after 4200 hours of cyclic aging test, the super weather-resistant polyester hot-dip galvanized composite coating system has a rust level of Ri0 and a peeling level of S0. This shows that the composite coating system can provide long-term protection for steel in CX environment, and the hot-dip galvanized layer in the coating system can provide good electrochemical protection for the exposed substrate at the scratches, that is, when the steel substrate is exposed due to slight scratches and bumps during installation and transportation, the coating system can still provide good protection for it.
[0179] Example 4
[0180] The difference between this embodiment and embodiment 1 is that the hot-dip coating is a hot-dip zinc-aluminum-magnesium coating.
[0181] The same performance test as in Examples 1-3 was conducted on Example 4, and the results showed that after 4200 hours of cyclic aging test, the rust level of the super-weather-resistant polyester zinc-aluminum-magnesium composite coating system was Ri0 and the peeling level was S0. However, it was found in the test that the zinc-aluminum-magnesium coating failed to provide reliable protection for the cut edges of steel.
[0182] Comparative Example 1
[0183] The photovoltaic support in this embodiment is provided with only one layer of polyester coating, and the coating thickness is 120 μm.
[0184] The same performance test as that of Examples 1-3 was carried out on Comparative Example 1, and the results obtained were: after 4200 hours of cyclic aging test, the rust registration of the polyester coating system was Ri2 and the peeling grade was S2.
[0185] With the above embodiments of the present invention as inspiration, through the above description, relevant personnel in this field can make various changes and modifications without departing from the technical idea of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the content of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A corrosion-resistant composite coating for offshore photovoltaic brackets, characterized in that: The composite coating comprises a hot-dip coating disposed on the surface of the photovoltaic support and a polyester powder coating disposed on the surface of the hot-dip coating; The hot-dip coating is selected from a hot-dip galvanizing layer and a zinc-aluminum-magnesium coating; The thickness of the hot-dip galvanized layer is 40-100 μm, and the coating mass of the hot-dip galvanized aluminum-magnesium layer is 250-300 g / m 2 , The thickness of the polyester powder coating is 100-150 μm.
2. The corrosion-resistant offshore photovoltaic support composite coating according to claim 1, characterized in that: The polyester powder coating is composed of the following components in parts by weight: Hyperbranched polyester resin 60%, curing agent 15%, leveling agent 1%, benzoin 0.5%, brightener 1%, titanium dioxide 20%, flaky pigment 6.5%, zinc phosphate hydrate 3.5%, organic corrosion inhibitor 0.5%, curing agent 21%, silane coupling agent 1%.
3. The corrosion-resistant offshore photovoltaic support composite coating according to claim 2, characterized in that: The preparation method of the hyperbranched polyester resin comprises the following steps: S1 esterification reaction: add terephthalic acid, neopentyl glycol, organotin catalyst and polymerization inhibitor into the reaction vessel, raise the temperature to 180-220°C for esterification reaction, and the esterification reaction time is 8-10 hours; S2 polycondensation reaction: After the esterification reaction is completed, the temperature is lowered to 200~220℃, and isophthalic acid, polydimethylsilane and catalyst are added to carry out polycondensation reaction. The reaction time is 6~8h.
4. The corrosion-resistant offshore photovoltaic support composite coating according to claim 2, characterized in that: The organotin catalyst is a sulfur-containing catalyst, and is selected from dibutyltin isooctyl dithioacetate, dimethyltin isooctyl dithioacetate, and dioctyltin isooctyl dithioacetate; The polymerization inhibitor is selected from one of p-hydroxyanisole and 2-tert-butylhydroquinone.
5. The corrosion-resistant offshore photovoltaic support composite coating according to claim 3, characterized in that: In the step S1, the amount of the organic tin catalyst added is 0.01-0.05% of the total mass of terephthalic acid and neopentyl glycol, the amount of the polymerization inhibitor added is 0.001%-0.1% of the total mass of terephthalic acid and neopentyl glycol, and the molar ratio of terephthalic acid to neopentyl glycol is 1:
2.
6. The corrosion-resistant offshore photovoltaic support composite coating according to claim 3, characterized in that: The molar ratio of the amount of isophthalic acid added in step S2 to the amount of terephthalic acid added in step S1 is 1:
1.
7. The corrosion-resistant offshore photovoltaic support composite coating according to claim 3, characterized in that: The amount of polydimethylsilane added in step S2 is 1-5% of the product in step S1.
8. A corrosion-resistant composite coating for offshore photovoltaic brackets, characterized in that: The catalyst in step S2 is a mixture of titanium alkoxide, tin oxide, antimony trioxide and cadmium acetate, with a molar ratio of 1:0.5:0.3:0.
6.
9. The corrosion-resistant offshore photovoltaic support composite coating according to claim 2, characterized in that: The preparation method of the polyester powder comprises the following steps: 1) Prepare the above raw materials in proportion, feed them in layers, and pre-mix them at high speed; 2) Melt mixing extrusion: The extrusion temperature of the twin screw zone 1 is 100~120℃, the extrusion temperature of the second zone is 120~130℃, the extrusion temperature of the third zone is 110~120℃, the main screw frequency is 40~50HZ, and the feeding speed is 25~40hz; 3) Cool and crush the tablets into pieces with a thickness of 1~2mm and an average area of 1±0.2cm 2 The flakes are ground into polyester powder.
10. A method for preparing a corrosion-resistant offshore photovoltaic support composite coating according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: S1 The solar photovoltaic bracket is hot-dip galvanized and then surface treated before spraying, which specifically includes the following steps: 1) Hot-dip galvanizing process: The workpiece is placed in hydrochloric acid with corrosion inhibitor and degreasing agent added to remove oil and rust on the surface of the workpiece, then rinsed with clean water, and then immersed in a mixed plating solution of ammonium chloride and zinc chloride. After being taken out and dried, it is placed in a molten zinc solution at a temperature of 435~455℃ for 2~10 minutes. After being taken out, it is placed in clean water at a temperature not exceeding 60℃ to cool, and then taken out and drained; 2) Surface treatment before spraying: chemical treatment is adopted. The workpiece is driven into the channel of the spray device through the conveyor chain. After 1.5 minutes of high-pressure spraying at 0.1Mpa, each process is cleaned in turn. First, it enters the degreasing process. The degreasing liquid is diluted with water in proportion and heated to 50°C. Then, the degreasing liquid remaining on the surface is rinsed with tap water. Finally, it is rinsed with tap water to avoid the residue of phosphating liquid. After rinsing, the workpiece enters the 80°C drying channel. After drying the residual moisture on the surface, it enters the next process; S2 spray polyester powder coating; S3 baking.
Citation Information
Patent Citations
Photovoltaic plate frame corrosion resistance treatment method
CN104831205A
Polyester powder coating with super penetration resistance and super weather resistance and preparation process of polyester powder coating
CN109679466A
Preparation method and application of weather-resistant polyester resin
CN117700699A
Photovoltaic support of long-acting anti-corrosion galvanized steel pile structure
CN218060441U
